Ophthalmologic adverse events in childhood head and neck rhabdomyosarcoma survivors treated according to four different local treatment strategies - Michele Morfouace; Marinka L.F. Hol; Natalia Arruti; Richard Bowman; Frederic Kolb; Veronique Minard; Bradley Pieters; Mark Gaze; Henry Mandeville; Eric Sandler; Ludwig E. Smeele; Julie Bradley; et al. (EJC Paediatric Oncology)
Introduction: Ophthalmological adverse events (OAEs) are known to frequently occur following local treatment for pediatric head and neck rhabdomyosarcoma (HNRMS). The exact nature of these OAEs and the burden they put on survivors is less well described. Moreover, it is suspected there might be differences in the prevalence and nature of OAEs depending on local treatment strategy applied: external beam radiation therapy with photons, external beam radiation therapy with protons, macroscopically radical surgery combined with brachytherapy, or microscopically radical surgery combined with external beam radiation therapy. Methods: We cross-sectionally assessed 98 HNRMS survivors with long (median 9 years) follow-up time, according to a predefined list of OAEs based on the Common Terminology Criteria for Adverse Events system. We added information from chart reviews on the nature and management of all OAEs scored grade ≥1. We describe the prevalence of OAEs for the different tumor sites and treatment strategies separately. Results: OAEs occurred following treatment of all HNRMS sites. The most frequently observed OAEs are eyelid abnormalities, dry eyes, and cataracts. Sixty-two percent of survivors had several different OAEs simultaneously. In 27 % of survivors additional (surgical) treatment of OAEs was required during follow-up. The patterns observed suggest a possible relationship between OAE type and treatment strategy. Conclusion: OAEs in HNRMS survivors confer a high burden of chronic toxicity. The simultaneous occurrence of multiple OAEs in individual survivors present a particularly challenging clinical scenario and demand specific expertise. We propose a standardized screening scheme to detect possible OAEs in asymptomatic survivors based on primary tumor localization.